2017
DOI: 10.1556/0806.45.2017.005
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of late sown wheat to exogenous application of silicon

Abstract: Late planting of wheat in rice-wheat cropping system is perhaps one of the major factors responsible for low crop yield. The main cause of reduction in yield is due to supra-optimal conditions during the reproductive growth. High temperature during reproductive phase induces changes in water relations, decreases photosynthetic rate, and transpiration rate, stomatal conductance and antioxidative defence system. Silicon (Si), being a beneficial nutrient not only provides significant benefits to plants growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 53 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…G9 and MS1 varieties showed highest stability (4%) when compared with the other varieties. Our results agree with Gong et al (2005) and Sattar et al (2017) who stated that silicon appears to be involved in the fortification of plants against oxidation of cell membranes, leading to the protection of cell structures than various plant structures. Liang et al (2007) concluded that using Si leads to its deposition in cell membrane, certification and hardening beside decrease of membrane damage in shoots; without Si cell membrane is hurt and material leakage from cell to outside increases.…”
Section: Effect Of (Si) Treatments On Stability Of Membranesupporting
confidence: 93%
See 1 more Smart Citation
“…G9 and MS1 varieties showed highest stability (4%) when compared with the other varieties. Our results agree with Gong et al (2005) and Sattar et al (2017) who stated that silicon appears to be involved in the fortification of plants against oxidation of cell membranes, leading to the protection of cell structures than various plant structures. Liang et al (2007) concluded that using Si leads to its deposition in cell membrane, certification and hardening beside decrease of membrane damage in shoots; without Si cell membrane is hurt and material leakage from cell to outside increases.…”
Section: Effect Of (Si) Treatments On Stability Of Membranesupporting
confidence: 93%
“…Similar conclusion was obtained by Gao et al (2006) noticed that the addition of Si increased water use efficiency by reducing leaf transpiration because silica-cuticle double layer formed on leaf epidermal tissue, the water flow rate in the xylem vessel and increased leaf water potential in potted wheat. Also, Sattar et al (2017) stated that application of Si enhanced the osmotic, relative water contents, turgor and water potential of wheat (T. aestivum) flag leaf, deposition of (Si) on leaf surface might reduce transpiration through controlling molecules of water.…”
Section: Effect Of (Si) Treatments On Relative Water Contentmentioning
confidence: 99%
“…Vertical bars represent standard error (SE) (n = 4). et al (2016) and Sattar et al (2017), who proved that Si fertilization in cacao and wheat plants interfered in stomatal dynamics and photochemical reactions, therefore regulating photosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, various studies have exposed that by absorbing Si, photosynthetic pigments can be increased in various plant species (Hasanuzzaman et al, 2018;Merwad et al, 2018). The application of Si on wheat (T. aestivum) plants showed better result by improving the leaves chlorophyll content (Ma et al, 2016), and photosynthesis rate (Sattar et al, 2017). Likewise, Maghsoudi et al (2016) demonstrated that Si leaf application increased photosynthesis pigments (chlorophyll a, b and total land carotenoids) and chlorophyll stability index (CSI) in different wheat (T. aestivum) cultivars under drought conditions.…”
Section: Silicon-mediated Improvement In Plant Growth Biomass and Photosynthesis Under Drought Stressmentioning
confidence: 99%
“…Generally, plants maintain a high water level through osmotic adjustment under dry stress circumstances (Blum, 2017). Although, high drought circumstances trigger a considerable reduction in water content of leaf including water potential in various plants (Abid et al, 2018 Application of Si enhanced the osmotic, relative water contents, turgor and water potential of wheat (T. aestivum) flag leaf (Sattar et al, 2017). Such as the water content of wheat (T. aestivum) was increased during drought (Ratnakumar et al, 2016).…”
Section: Regulating Osmotic Potentialmentioning
confidence: 99%